Legal Awareness and Compliance with Halal Certification in Micro, Small, and Medium Enterprises (MSMEs) of Fast Food in Kerinci Regency - Susilawati, Susilawati; Fauzi, Muhammad; Arzam, Arzam (Mutawasith: Jurnal Hukum Islam, 2024)
The legal awareness of fast food MSMEs regarding halal certification in Kerinci Regency is an important topic with the majority of the population being Muslim. However, the low level of legal awareness regarding halal certification can hinder the progress of MSMEs. This study aims to examine the level of legal awareness of fast food MSME players regarding halal certification in Kerinci Regency. Testing the level of legal awareness in terms of knowledge, understanding, attitudes and behavior. This research uses quantitative descriptive method. The research data were collected from primary data in the form of questionnaires distributed and answered by 100 fast food MSME actors, using descriptive analysis as a data analysis tool. The results showed that the level of legal awareness of fast food MSME players in Kerinci Regency is very low, where it can be seen that the value or percentage in terms of knowledge, understanding, attitude and behavior is very low. The findings of this study underscore the need for an effort and method/strategy to increase the legal awareness of fast food MSME players regarding halal certification so that it can provide a breakthrough and at the same time have implications in supporting ongoing halal developments.